2019
DOI: 10.1101/849661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A highly sensitive and specific SYBR Green quantitative polymerase chain reaction (qPCR) method for rapid detection of scale drop disease virus in Asian sea bass, Lates calcarifer

Abstract: Scale drop disease virus (SDDV) is a novel Megalocytivirus causing scale drop disease (SDD) in Asian sea bass in Southeast Asia. In order to support disease diagnosis and surveillance, the present study developed a highly sensitive and specific SYBR Green qPCR assay for rapid detection of SDDV. Specific primers targeting a 135-bp fragment of ATPase coding gene of the SDDV genome were newly designed and subsequent gradient PCR assays were conducted to investigate their optimal annealing temperature. The optimiz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Detection of SDDV in multiple types of samples (seven destructive and three non-destructive) implied that SDDV infection is systemic during a clinical disease outbreak as previously suggested (Sriisan et al, 2020). Moreover, the presence of the virus in blood and mucus of all tested samples suggested that infected fish (both clinically sick and subclinical) from a disease outbreak can shed the virus to both systemic and mucosal systems similar to that of other viruses in finfish such as TiLV in tilapia (Chiamkunakorn et al, 2019;Liamnimitr et al, 2018) and ISAV in salmon (Aamelfot et al, 2015;Giray et al, 2005).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Detection of SDDV in multiple types of samples (seven destructive and three non-destructive) implied that SDDV infection is systemic during a clinical disease outbreak as previously suggested (Sriisan et al, 2020). Moreover, the presence of the virus in blood and mucus of all tested samples suggested that infected fish (both clinically sick and subclinical) from a disease outbreak can shed the virus to both systemic and mucosal systems similar to that of other viruses in finfish such as TiLV in tilapia (Chiamkunakorn et al, 2019;Liamnimitr et al, 2018) and ISAV in salmon (Aamelfot et al, 2015;Giray et al, 2005).…”
Section: Discussionsupporting
confidence: 51%
“…All fish were alive after sample collection. In order to confirm that the positive sample(s) was truly positive, the positive sample(s) was then assayed with the SYBR Green quantitative polymerase chain reaction (qPCR) method according to Sriisan et al (2020).…”
Section: Application Of Blood Sample For Sddv Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracted DNA was tested by conventional polymerase chain reaction (cPCR) using published primer sequences and methods for the novel Vibrio spp. that cause "big belly" disease (Gibson-Kueh et al, 2021;Segers & Grisez, 2005), Vibrio harveyi (Pang et al, 2006), Streptococcus iniae (Torres-Corral & Santos, 2021), scale drop disease virus (SDDV) (Sukhontip et al, 2019) Note: Fish were fasted 1-2 days prior to transfers. Neither sedation nor ammonia-binding additives were used during transport.…”
Section: Pcrmentioning
confidence: 99%